2004
DOI: 10.1097/00004836-200404000-00007
|View full text |Cite
|
Sign up to set email alerts
|

40 mg Pantoprazole and 40 mg Esomeprazole Are Equivalent in the Healing of Esophageal Lesions and Relief from Gastroesophageal Reflux Disease???related Symptoms

Abstract: In patients with gastroesophageal reflux disease, 40 mg pantoprazole daily and 40 mg esomeprazole daily are equally effective for healing of esophageal lesions and relieving gastroesophageal reflux disease-related symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
50
0
5

Year Published

2004
2004
2014
2014

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(58 citation statements)
references
References 22 publications
3
50
0
5
Order By: Relevance
“…Both drugs were safe well-tolerated. 18 Gillessen et al 19 and Scholten et al 20 have reported similar effectiveness for esomeprazole 40 mg and pantoprazole 40 mg, or even greater effectiveness for latter drug in terms of speed of symptom resolution. Crossover studies in healthy subjects and patients with symptoms of GERD have shown that esomeprazole is more effective than all other PPI for providing greater time with pH >4.…”
Section: Discussionmentioning
confidence: 94%
“…Both drugs were safe well-tolerated. 18 Gillessen et al 19 and Scholten et al 20 have reported similar effectiveness for esomeprazole 40 mg and pantoprazole 40 mg, or even greater effectiveness for latter drug in terms of speed of symptom resolution. Crossover studies in healthy subjects and patients with symptoms of GERD have shown that esomeprazole is more effective than all other PPI for providing greater time with pH >4.…”
Section: Discussionmentioning
confidence: 94%
“…However, to date there is no undisputed evidence of an appreciable difference in effectiveness between different PPIs at equivalent doses. In fact, clinical studies have not demonstrated any consistent difference between PPIs at similar doses with regard to clinical or endoscopic outcomes [2,15,16,17, 28]. …”
Section: Discussionmentioning
confidence: 99%
“…Esomeprazole and pantoprazole are both very effective and prove therapeutic equivalence in case of GERD [15,16,17], and are indicated for the treatment of enGERD, achieving adequate short-term symptom relief rates, particularly heartburn, and effective subsequent long-term symptomatic remission rates [18,19,20,21]. However, the prime concerns for many GERD patients, particularly for those with enGERD, are fast relief of pain and subsequently sustained symptom control, and therefore not only relief rates at a fixed date (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Clinically, however, there appears to be no significant or consistent differences between the five available PPIs in terms of improving the symptoms or endoscopic healing of mucosal breaches when the PPIs are tested at similar doses [17]. …”
Section: The Evolution Of Gastrinmentioning
confidence: 99%